(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
The article presents the cases of acute poisoning from the mixture of polyatomic alcohols in the solvent "Razbavitel" in the secretions isolated from the biological object, biological fluid and physical evidence. Microcrystallographic reactions, color-forming reactions, and gas liquid chromatography methods were developed in the obtained separations. It was observed that the retention time of polyatomic alcohols in the solvent "Razbavitel" in the chromatogram was compared with the samples taken from biological objects and biofluids.